Efficacy of photodynamic therapy using TiO2 nanoparticles doped with Zn and hypericin in the treatment of cutaneous Leishmaniasis caused by Leishmania amazonensis - Sepúlveda, Alex Arbey Lopera; Arenas Velásquez, Angela Maria [UNESP]; Patiño Linares, Irwin Alexander; de Almeida, Leticia [UNESP]; Fontana, Carla Raquel [UNESP]; Garcia, Claudia; Graminha, Marcia Aparecida Silva [UNESP] (Elsevier, 2020)
Since Leishmania parasites exhibit resistance outbreaks to drugs conventionally used in medical treatments, research of new antileishmanial compounds or alternative treatment therapies are essential. A focus of interest has been the implementation of light-based therapies such as photodynamic therapy, where inorganic compounds such as titanium dioxide have shown promising results as drug delivery carriers. In this work, nanoparticles of TiO2 doped with Zn (TiO2/Zn) were synthesized through solution combustion route and with hypericin (HY) in order to enhance its photodynamic activity in the visible light region. Scanning (SEM) and transmission (TEM) electron microscopy analyses showed particles of (TiO2/Zn) with sizes smaller than 20 nm and formation of aggregates smaller than 1 μm, whilst electron diffraction spectroscopy (EDS) analysis ensured the presence of Zn in the system. The association of the TiO2/Zn with HY (TiO2/Zn-HY) was further confirmed by fluorescence spectrometry. Measurements of its cellular uptake showed the presence of smaller molecules into promastigotes after 120 min incubation. TiO2/Zn-HY showed good antileishmanial activity (EC50 of 17.5 ± 0.2 μg mL−1) and low cytotoxicity against murine macrophages (CC50 35.2 ± 0.3 μg mL−1) in the visible light (22 mW cm-2; 52.8 J cm-2). Moreover, in the in vivo analysis, TiO2/Zn-HY decreased the parasite load of L. amazonensis - BALB/c infected mice by 43% – 58% after a combination of blue and red light presenting 22 mW cm-2 of intensity and 52.8 J cm-2 of fluency delivered. All together, these data indicate a new combined system of nanoparticles associated with a photosensitizer and PDT as alternative to amphotericin B for the treatment of cutaneous leishmaniasis.
Keywords: Cutaneous leishmaniasis; Hypericin; Leishmania amazonensis; Nanoparticles; Photodynamic Therapy (PDT); Reactive oxygen species (ROS); Titanium